Team cohesion and its impact on individual and team performance in Ethiopian Premier League volleyball clubs - Worku, Meseret M.; Adane, Alemmebrat K.; Admasu, Belayneh C. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to examine the level of team cohesion, the relationship between cohesion and performance, and the key determinants of task and social cohesion in relation to individual and team performance among Ethiopian Premier League volleyball teams. A descriptive, cross-sectional research design was employed. The participants consisted of 51 players who actively competed during the 2020/2021 season. Data were collected using the Group Environment Questionnaire (GEQ) and analyzed with SPSS version 26. The findings revealed moderately high levels of cohesion across all four dimensions. A positive relationship was found between cohesion and performance; however, only task cohesion dimensions showed a significant correlation with team performance. Specifically, Attraction to Group-Task (ATG-T) was significantly associated with individual performance (r = .327, p < .05), and Group Integration-Task (GI-T) was strongly correlated with both individual and team performance (r = .596, p < .01). Overall, task cohesion was identified as a significant predictor of player performance (p < .05), while social cohesion showed no significant relationship (p > .05). Based on these findings, it is suggested that stakeholders develop strategies and organize social activities to enhance social cohesion, particularly within women’s Premier League volleyball teams.